Linguagem é meio, (des)manipulação é fim? - Kist, Eliane (2020)
In this research, based on the theoretical assumptions of the French Discourse Analysis, we seek to analyze the discursive movements imbricated in the process of "dismanipulation" of headlines in the Big Media, undertaken by the Pen Dismanipulating page, with the aim of understanding the meaning effects of what we understand as a linguistic contrast, resulting from his intervention on the headlines. To understand the meaning effects of this linguistic contrast, we observe the positions occupied in the discursive process, in order to apprehend, from the discursive confrontation operated in the process of (de) manipulation, the way in which each subject position manages, through language, interdiscourse, memory and meaning to support and legitimize his speech. For this research, we constituted a corpus with 48 ―unmanipulated‖ headlines that circulated between 2016 and 2018 on the Caneta Desmanipuladora pages on Facebook and Twitter. From this set of materialities, we made a methodological approach by selecting ten headlines on which our analysis focused. From this study, we can infer that the reflections operated by the Dismanipulating Pen produce a displacement of meaning, the result of the work of the ideology that is in charge of producing the effect of evidence in the subject and in his imaginary relationship with language, and that guides the discourses. Thus, we understand that the ―dismanipulation‖ work done by the page is not simply a journalistic reissue, but a discursive confrontation around the names of socio-political events. And his intervention consists exactly in disturbing the order established by the hegemonic discourse, accentuating the lines of cleavage, in an attempt to deconstruct its literality. Thus, we propose to discuss how this process of producing evidence is constituted in the discourse of the media and how they are inscribed in the process of producing meanings through the ideological mechanism of erasing the process of interpellation / identification in the form of autonomy.